Behavioral and physiological effects of Viola spp. cyclotides on Myzus persicae (Sulz.). (April 2020) - Dancewicz, Katarzyna; Slazak, Blazej; Kiełkiewicz, Małgorzata; Kapusta, Małgorzata; Bohdanowicz, Jerzy; Gabryś, Beata
Graphical abstract: Highlights: Cyclic polypeptides – cyclotides – are involved in plant defense. Cyclotides from Viola odorata show deterrent activities against Mysus persicae. Cyclotides appear to affect the aphid gustatory organs and digestive system. Cyclic polypeptides play an important role in the plant-aphid interactions. Abstract: Cyclotides are defense peptides produced by several plant families. Viola spp. (Violaceae) produce an array of cyclotides with varying biological activities. The peach potato aphid Myzus persicae (Sulz.) (Hemiptera: Aphididae) is a generalist that feeds on the secondary hosts of over 40 plant families, including Violaceae. The present work aimed to evaluate the activities of cycloviolacins from Viola odorata L. and V. ulignosa Besser (cyO2, cyO3, cyO13, cyO19) against M. persicae . To investigate the peptides' influence on aphid feeding behavior, we used 20% sucrose diets supplemented with cyclotides and measured the effects with electrical penetration graph (EPG) technique. We also applied anti-cyclotide antibodies and immunohistochemistry to track the peptides in the digestive systems of the aphids. Our study shows that cyclotides affect aphid probing and feeding behavior and limit their diet sap uptake. The cycloviolacin cyclotides: cyO13 (100 µM) and cyO19 (50 µM) most strongly impeded aphid ingestion activities when applied in sucrose diet. Sustained ingestion of the diet was blocked by 100 µM cyO13, and no aphid showed ingestion of the diet for longer than 10 min. Cyclotides were detected in the pharynx, in contact with the epipharyngeal gustatory organ, in the stomach (midgut) and upper intestine. The present study shows the deterrent activity of cycloviolacins on M. persicae . This activity may be related to the peptides' effects on epithelial cells and gustatory organs along the aphid digestive system. We demonstrate that cyclotides may play an important role in plant-aphid interactions.